Application of Foam Mat Drying for the Production of Tempoyak Powder - Utama, Rozi Satria; Fajri, Prima Yaumil; Azel, Farid (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
The production of tempoyak powder is a significant attempt to preserve tempoyak. Therefore, this study aimed to determine the proper amount of albumin and maltodextrin to produce tempoyak powder using foam mat drying. This study was divided into two stages, namely producing tempoyak powder by foam mat drying method and determining the characteristics. In the production, egg albumin was used as foaming agent in three concentrations, namely 10%, 15%, and 20%, as well as maltodextrin as a filler in 0% and 5%. Chemical and physical characteristics, such as proximate test, pH, total titrated acid, bulk and tap density, Carr Index (CI), and Hausner Ratio (HR) were investigated. The result showed that moisture content of tempoyak powder ranged from 10.22 to 13.34%. Tempoyak powder with 20% albumin but no maltodextrin had the lowest moisture content. Furthermore, the addition of albumin without maltodextrin increased foam overrun, accelerating drying process and powdered tempoyak with lower moisture concentration. The addition of maltodextrin decreased foam tempoyak overrun, causing drying process to be slower. Tempoyak powder had protein content ranging from 8.71 to 13.12%, and with 20% albumin and no maltodextrin, the highest protein level of 13.12% was obtained. Fat content ranged from 6.99 to 8.15%, with the highest observed in tempoyak powder with 20% albumin and no maltodextrin. The addition of albumin as foaming agent increased protein and fat content. Furthermore, the total titrated acid in powdered tempoyak products was not significantly different from fresh tempoyak. The result suggested that the acid content does not considerably reduce while drying. Tempoyak powders had CI and HR values that ranged from good to excellent, showing good flowability and cohesiveness.